2009
DOI: 10.1186/1471-2334-9-165
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of medically attended adverse events following tetanus and diphtheria toxoid vaccine in adolescents and young adults: a Vaccine Safety Datalink study

Abstract: BackgroundLocal reactions are the most commonly reported adverse events following tetanus and diphtheria toxoid (Td) vaccine and the risk of local reactions may increase with number of prior Td vaccinations.MethodsTo estimate the risk of medically attended local reactions following Td vaccination in adolescents and young adults we conducted a six-year retrospective cohort study assessing 436,828 Td vaccinations given to persons 9 through 25 years of age in the Vaccine Safety Datalink population from 1999 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…12 A VSD retrospective cohort study of 436 828 Td vaccinations demonstrated that medically attended local reactions, including cellulitis, were more common among persons who received a Td-containing vaccine within the last 5 years compared with a longer interval. 13 Another study assessed safety in 4524 Tdap-vaccinated health care workers during a pertussis outbreak in New England. 14 Overall, there was no difference in the rates of solicited moderate or severe injection site reactions, but there was an increase in redness, swelling, and subjective fever among patients who had received their prior Td-containing vaccine less than 2 years earlier.…”
Section: Discussionmentioning
confidence: 99%
“…12 A VSD retrospective cohort study of 436 828 Td vaccinations demonstrated that medically attended local reactions, including cellulitis, were more common among persons who received a Td-containing vaccine within the last 5 years compared with a longer interval. 13 Another study assessed safety in 4524 Tdap-vaccinated health care workers during a pertussis outbreak in New England. 14 Overall, there was no difference in the rates of solicited moderate or severe injection site reactions, but there was an increase in redness, swelling, and subjective fever among patients who had received their prior Td-containing vaccine less than 2 years earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of reported adverse events from diphtheria toxoid–containing vaccines varies by vaccine formulation, dose of diphtheria toxoid, prior vaccination history, and prevaccination antidiphtheria toxoid antibody levels. Although local injection-site reactions are common, only a small proportion of these are clinically significant ( 226 ). Administration of diphtheria toxoid has not been associated with anaphylaxis.…”
Section: Vaccines For Prevention Of Pertussis Tetanus and Diphtherimentioning
confidence: 99%
“…Injection site reactions, allergic reactions (evaluated separately in the outpatient, ED, and inpatient settings), syncope, and nonspecific reactions (eg, adverse effect of viral vaccines) were considered common (Table 1). 14…”
Section: Ascertainment Of Adverse Eventsmentioning
confidence: 99%